VILLAGE HEAD OF PERFORMANCE EVALUATION IN DEVELOPMENT IMPLEMENTATION VILLAGE (Studies In the village of Upper Subdistrict Ranoketang Touluan Southeast Minahasa Regency) - TAMPONGANGOY, CHRISTINE; POSUMAH, JOHNNY HANNY; Londa, Very (Sam Ratulangi University, 2016)
ABSTRACT : The success or failure Increased development in the village is very much determined by thevillage head, the extent to which the head of the village to plan, mobilize, motivate, direct, communication,organizing, implementing, in relation to the management means for providing leadership managementfunction or as a manager in a management , In connection with the process of rural development, in theprocess of rural development consists of two main elements, namely and development that the communityand the government. The village head in this very important role in the development of the village wherethe village head who are leaders in the village as well as the discount formal duties and obligations incarrying out the task of managing the construction of PP 72 Th, 2005.During the development program plan drawn / assigned for this in accordance with the aspirations of thelocal community needs, and development programs undertaken by the government during the year,namely the collection / procurement matrial construction of the village office, casting shoulders villageroad through the village fund, improving the economy of the community, with encourage people tomaximize the potential of rice paddies and fields, through the planting of rice 2 times per year, the potentialof the lake, encouraging the community to arisan home, who do not have homes, and other forms offinancial arisan (guard / hamlet) for coaching and learning to save.Keywords: Village Head Performance, Implementation of Rural Development.